Heritability and risks associated with early onset hypertension: multigenerational, prospective analysis in the Framingham Heart Study. (12th May 2017) - Niiranen, Teemu J; McCabe, Elizabeth L; Larson, Martin G; Henglin, Mir; Lakdawala, Neal K; Vasan, Ramachandran S; Cheng, Susan
Abstract : Objective  To determine the role of early onset versus late onset hypertension as a risk factor for hypertension in offspring and cardiovascular death. Design  Multigenerational, prospective cohort study. Setting  Framingham Heart Study. Participants  Two generations of community dwelling participants with blood pressure measurements performed at serial examinations spanning six decades: 3614 first generation participants with mortality data and 1635 initially non-hypertensive second generation participants with data available on parental blood pressure. Main outcome measures  The main outcome measures were relation of parental early onset hypertension (age <55 years) with incidence of hypertension in offspring, using regression analyses, and relation of age at hypertension onset with cause specific mortality using a case (cardiovascular death) versus control (non-cardiovascular death) design. Results  In second generation participants, having one or both parents with late onset hypertension did not increase the risk of hypertension compared with having parents with no hypertension; by contrast, the hazard ratios of hypertension were 2.0 (95% confidence interval 1.2 to 3.5) and 3.5 (1.9 to 6.1) in participants with one and both parents with early onset hypertension, respectively. In first generation decedents, 1151 cardiovascular deaths occurred (including 630 coronary deaths). The odds of cardiovascular death increased linearly with decreasing age of hypertension onset (P<0.001 for trend). Compared with non-hypertensive participants, hypertension onset at age <45 years conferred an odds ratios of 2.2 (1.8 to 2.7) for cardiovascular death and 2.3 (1.8 to 2.9) for coronary death, whereas hypertension onset at age ≥65 years conferred a lower magnitude odds ratios of 1.5 (1.2 to 1.9) for cardiovascular death and 1.4 (0.98 to 1.9) for coronary death (P≤0.002 for differences in odds ratios between hypertension onset at age <45 and age ≥65). Conclusions  Early onset and not late onset hypertension in parents was strongly associated with hypertension in offspring. In turn, early onset compared with late onset hypertension was associated with greater odds of cardiovascular, and particularly coronary, death. These findings suggest it may be important to distinguish between early onset and late onset hypertension as a familial trait when assessing an individual's risk for hypertension, and as a specific type of blood pressure trait when estimating risk for cardiovascular outcomes in adults with established hypertension.